2010
DOI: 10.1590/s0034-89102010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Impact on human health of particulate matter emitted from burnings in the Brazilian Amazon region

Abstract: Impact on human health of particulate matter emitted from burnings in the Brazilian Amazon regionImpactos na saúde humana de partículas emitidas por queimadas na Amazônia brasileira ABSTRACT OBJECTIVE: To analyze the impact on human health of exposure to particulate matter emitted from burnings in the Brazilian Amazon region. METHODS:This was an ecological study using an environmental exposure indicator presented as the percentage of annual hours (AH%) of PM 2.5 above 80 μg/m 3 . The outcome variables were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
36

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 21 publications
2
86
0
36
Order By: Relevance
“…In terms of adverse health effects, several respiratory problems resulting from the acute inhalation of PM were witnessed in the Southeast Region and in the Brazilian Amazon in both children and the elderly 107,108,109 . Air pollution has a direct effect on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adverse health effects, several respiratory problems resulting from the acute inhalation of PM were witnessed in the Southeast Region and in the Brazilian Amazon in both children and the elderly 107,108,109 . Air pollution has a direct effect on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…6 There are few Brazilian studies which assess the effects of exposure to aerosols from burning biomass on cardiorespiratory function and mortality in children and elderly in the Brazilian Amazon. 8,12 Research applying to the Amazon region has only recently been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In the same region of the study, some authors observed an increase of morbidity and mortality during the same period. They approached that such advance is associated with increase of air pollutants related to the prevalence of biomass burns in the region 16,[29][30][31] . Urban waste burning, which is a common practice in Cuiabá and Várzea Grande, can also contribute to the concentration increase of air pollutants, as well as to their toxicity, because they present more proximity of the individual and have a great mixture of toxic components (plastic, fuel, electronic device) 32 .…”
Section: Discussionmentioning
confidence: 99%